CONTRIBUCIÓN DEL DERECHO EUROPEO A LA LUCHA CONTRA LA DISCRIMINACIÓN RETRIBUTIVA: SU ESPECIAL INCIDENCIA EN EL CASO ESPAÑOL - Hermosilla, Olimpia Molina (European Scientific Journal, ESJ, 2013)
The average wages received by women are lower than those received by men for doing the same work or work of equal value in all European countries, to the extent that we are facing one of the most obvious and persistent signs of workplace discrimination suffered by women with regard to men, although it is not the only one; difficulties in access and working conditions, sectoral and occupational segregation, or the negative impact on female employment rates caused by the absence of co-responsibility policies in tasks of childcare and care of dependent persons, are clear signs of the continued disadvantage that, even today, still affects all women in the European Union compared to men; a disadvantage that is felt with greater or lesser intensity depending on the Member State under consideration. This situation is noted particularly severely in those Member States that are still suffering today in their labour market the negative consequences of the economic and financial crisis that has been affecting Europe in recent years, as in the particular case of Spain. The persistence and magnitude of this manifestation of labour discrimination suffered by women has led to the appearance of the term ―gender pay gap‖, to denote the indicator that measures the relative difference between average gross hourly earnings for work obtained by women and men, considering the economy as a whole. The purpose of this study is to highlight the contributions of European Law and of the doctrine established by the Court of Justice of the European Union, that are being made to reduce this wage gap, as well as the impact that one and the other has internally in the Member States, with particular reference to the study of this question in the case of Spain, due to the worrying reverse being suffered by the right to effective equality between women and men in terms of access and participation in the labour market in this country in recent years.